Kinematics and Kinetics of Multiple Sets Using Lifting Straps During Deadlift Training. Issue 12 (December 2015) - Coswig, Victor S.; Machado Freitas, Diogo Felipe; Gentil, Paulo; Fukuda, David H.; Del Vecchio, Fabrício Boscolo
Abstract : Abstract: Coswig, VS, Freitas, DFM, Gentil, P, Fukuda, DH, and Del Vecchio, FB. Kinematics and kinetics of multiple sets using lifting straps during deadlift training. J Strength Cond Res XX(X): 000–000, 2015—The deadlift is a fundamental exercise used in the development of whole body strength and a common element in resistance training programs for all levels. However, many practitioners report the fatigue of forearm muscles and possibly a lack of grip strength as obstacles to exercise performance, which may lead to the use of ergogenic aids, such as lifting straps. The objective of this study was to evaluate kinematic variables during the execution of multiple sets of deadlift with (WS) and without (NS) lifting straps. Eleven subjects (25 ± 3.3 years) with an average of 4 ± 2.6 years of resistance training experience were enrolled in the study. After the 1 repetition maximum (1RM) test WS and NS, subjects performed separate trials of 3 sets to failure at 90% of 1RM in a counterbalanced fashion. With straps resulted in lower speed (0 to −25%) (−3 to −10%) and greater force (20–28%) and duration (concentric phase: 0–13%) when compared with NS. Therefore, it is concluded that the use of straps directly influences exercise performance that requires manual grip strength, increasing the amount of work performed by the target muscles.